Dynamic belonging : contemporary Jewish collective identities - Goldberg, Harvey E.; Cohen, Steven Martin; Kopelowitz, Ezra (Berghahn Books, 2012)
World Jewry today is concentrated in the US and Israel, and while distinctive Judaic approaches and practices have evolved in each society, parallels also exist. This volume offers studies of substantive and creative aspects of Jewish belonging. While research in Israel on Judaism has stressed orthodox or "extreme" versions of religiosity, linked to institutional life and politics, moderate and less systematized expressions of Jewish belonging are overlooked. This volume explores the fluid and dynamic nature of identity building among Jews and the many issues that cut across different Jewish g.